A Fracture of Unilateral Pars Interarticularis of the Axis: A Case Report - Aydin, Keramettin; Cokluk, Cengiz (Turkish Neurosurgical Soc, 2007)
OBJECTIVE: To present a case of a fracture of the unilateral pars interarticularis of the C2. METHODS: There is confusion in the use of anatomic terminology of the pars interarticularis and pedicle of the C2 in literature. A fracture of the unilateral pars interarticularis of the C2 was diagnosed and treated nonsurgically by a Philadelphia collar. RESULT. The patient was free of pain and obtained a full range of motion. CONCLUSION: The presumed mechanism of injury in the fracture described here was hyperextension and axial loading.
Keywords: C2 Fracture; Unilateral Pars Interarticularis; Axis